Case report: Pyrotinib in the treatment of advanced scrotal EMPD combined with sweat gland carcinoma - Zhu, Liquan; Wang, Haoqiang; Cheng, Donghai; Wang, Wei; Lei, Yue; Yang, Ning; Peng, Lijun; Liu, Peng; Zhou, Juan; Xie, Bo (Frontiers in Oncology, 2024)
Extramammary Paget disease(EMPD) is a rare cutaneous intraepithelial adenocarcinoma, which is mostly distributed in areas with sweat gland cells, and mainly occurs in the anogenital skin of women.The male genital tract involvement is extremely rare, and often occurs with other malignant tumors.Paget's disease in the scrotum with sweat gland carcinoma is even more rare. In the first report of scrotal endocrine sweat gland carcinoma associated with Paget disease by Saidi JA in 1997, no more than 50 cases have been reported in the relevant research worldwide. Early EMPD combined with sweat gland carcinoma is mainly surgical treatment, and there is no standard treatment plan for advanced EMPD with sweat gland carcinoma. Previous article has reported that chemotherapy such as paclitaxel, fluorouracil, platinum, vinblastine and molecular targeted therapy based on the genetic test results of patients have certain efficacy. Here we report a 79-year-old male case diagnosed with HER-2 overexpression, which was effectively controlled by chemotherapy and anti-HER-2 treatment such as pyrotinib.